2014
DOI: 10.4236/ape.2014.42009
|View full text |Cite
|
Sign up to set email alerts
|

Hippotherapy in Children with Developmental Delays: Physical Function and Psychological Benefits

Abstract: Hippotherapy, or horse therapy, is an innovative form of physical therapy that involves the use of a horse as a therapeutic tool in order to effectively challenge a rider's core muscles. The rhythm of the horse's gait continuously engages the client's balance and posture, while the supervising physical therapist seeks to improve the client's overall coordination and fine motor skills through various activities. This combination of movement and therapist-directed activity can have significant impacts on the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(26 reference statements)
1
3
0
2
Order By: Relevance
“…[10], C. Bronson et al [11], Frevel et al [12], Lindroth et.al. [18], D. Silkwood-Sherer et al [13], Mr. Thompson et al [14] and Inna Ivanova et al [9] studies presented a significant improve in balance. Most of the studies used BBS as an evaluating tool.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10], C. Bronson et al [11], Frevel et al [12], Lindroth et.al. [18], D. Silkwood-Sherer et al [13], Mr. Thompson et al [14] and Inna Ivanova et al [9] studies presented a significant improve in balance. Most of the studies used BBS as an evaluating tool.…”
Section: Discussionmentioning
confidence: 99%
“…Torso and balance were examined by D. Silkwood-Sherer et al [13] study, in which the team receiving hippotherapy showed a statistically significant improvement from pretest (0 week) to posttest (14 weeks) for BBS [average increase of 9. In 2014, Mr. Thompson et al [14] conducted a study on torso and orthostatic control. The results showed that 62.5% (5/8) of individuals improved in the Orthostatic Scale score, 87.5% (7/8) reduced their time to complete the level and non-flat distances, and 50% (4/8) of participants showed better range results based on post-coordination.…”
Section: Balancementioning
confidence: 99%
“…Patients receiving hippotherapy usually show improvements in motor results because a horse's gait is very similar to that of a normal human walking pattern. Therefore, a person who cannot walk independently is able to assimilate this pattern through the horse's gait [17].…”
Section: Stress Management Through Hippotherapy In Children With Developmental Disordersmentioning
confidence: 99%
“…Οι δοκιμές περιλάμβαναν μια χρονομετρημένη απόσταση και μια δοκιμή βηματισμού. Τα αποτελέσματα έδειξαν ότι το 62,5% των υποκειμένων βελτιώθηκε αποδεικνύοντας ότι οι συνεδρίες ιπποθεραπείας είναι ένας πολύ αποτελεσματικός τρόπος για να βελτιωθεί η φυσική λειτουργία, ειδικά ο έλεγχος, η δύναμη και ο συντονισμός σε παιδιά που έχουν διαγνωστεί με οποιοδήποτε είδος αναπτυξιακής καθυστέρησης ή κινητικής διαταραχής (Thompson, Ketcham & Hall, 2014).…”
Section: αποτελέσματαunclassified